Pengembangan Media Pembelajaran Matematika Berbasis Geogebra pada Materi Garis Singgung Lingkaran untuk Siswa Kelas VIII SMP Negeri 1 Purwodadi - Mulyastuti, Indah Dwi, Dr. Sumardi, M.Si (2017)
The objective of this study are: (1) to know the procedure; (2) the worthiness; and (3) the effectiveness of math learning media based on geogebra on a tangent line to circle for second grade student at SMPN 1 Purwodadi. This study use research and development design. Data collection was done by questionnaire, pretest, and post test. The data were then analyzed with quantitative descriptive analysis which visualized by score and percentage, on paired sample T-test. The result of this study showed that: (1) the procedures are preliminary and prototyping step which use formative evaluation pathway; (2) the worthiness of this math learning media from material expert, media expert, learning practitioner, one-to-one, and small group are 88,281%; 77,084%, 89,06%; 85,42%; 84,72%, respectively; (3) hypothetical test obtain t_hit=3,4381>t_α=1,699; t_hit=3,4381∈DK, post test score is better than pretest. Based on that result, so the math learning media based on geogebra on a tangent line to circle is worth and have a potential effect to use for second grade student at SMPN 1 Purwodadi.